ANALYSIS OF ACUTE APPENDICITIS CLINICAL PATHWAYS IMPLEMENTATION IN ROYAL PRIMA MEDAN GENERAL HOSPITAL YEAR 2020 - Alexander Angkasa; Ermi Girsang; Ali Napiah Nasution; Adrian Khu; Sri Lestari Ramadhani Nasution (The Indonesian Journal of Public Health, 2022)
Introdution: Clinical pathway (CP) is a disease management tool used to reduce unnecessary variations in services, increase clinical outcomes, and control resources. Acute appendicitis is one cause of acute abdominal pain, where cases of appendix perforation range from 20-30% increasing to 32-72% at the age of more than 60. Methods: This research was conducted using mix method with case study design. Qualitative data were taken by interview and observation. Quantitative data were taken with a simple description from the acute appendicitis CP documentation in medical records and ICPAT (January - September 2020, n = 117). Result: According to the result of the research, the level of completeness for CP was 100% and form filling was 85%. Conclusion: ICPAT dimension 1 made sure that the form was the clinical pathway. The content and quality were good, and dimension 2 assesses the CP documentation process. The content is lacking and the quality is moderate, dimension 3 assess the CP development process which content was good, and quality was moderate, and dimension 4 assesses the CP implementation process. The content was moderate, and the quality was good. Dimension 5 is to assess the maintenance of clinical pathways in which content was lacking and quality was moderate. Dimension 6 serves to assess the role of the organization that content was good and quality was moderate where the obstacles were due to lack of understanding and time constraints.